Why storytelling matters...especially in mineral exploration. Issue 1 (1st December 2019) - Saleem, Ahmad; Beresford, Steve
Summary: There is an Indian proverb that goes: "Tell me the truth and I'll believe it for a while. But tell me a story and it will stay with me forever."